CEMENT BOND QUALITY ANALYSIS BASED ON CEMENT-BOND LOG (CBL) DATA: CEMENTING SQUEEZE OPERATION IN WELL X ZONE 7 IN - Zaidan Raden Syamsuri, Muhammad
Carbon Capture & Storage atau Carbon Capture, Utilization & Storage (CCS/CCUS) is an effort to reduce greenhouse gas emissions in Indonesia. As one of the highest contributors to greenhouse-gas emissions, Indonesia is taking serious steps to address this through several programmes. This CCS/CCUS program will be implemented at the X well, which will be converted from an exploration well to a CO2 injection well. The study will focus on the analysis and evaluation of the squeeze cementing process aimed at evaluating cement quality based on cement bond log and variable density log (CBL-VDL) data and bonding index analysis on the production liner zone. Through such an evaluation, it can be determined how the quality of cement in the X well and determine the good step, where cement can isolate CO2 from the surface. Through the studies that have been carried out, it can be concluded that there has been an improvement in the quality of cement bonding in the production zone of the liner although this improvement has not achieved the optimal result for achieving good bonding.